'It aye like London, you know': The Brexit Novel and the Cultural Politics of Devolution. Issue 1 (13th May 2020) - Ashbridge, Chloe
This paper takes Anthony Cartwright's The Cut (2017 ) as its central focus, a novel commissioned by European publisher Peirene Press as a fictional response to the UK's 2016 Brexit vote. I provide a discussion of what I term the 'cultural politics of devolution' in Cartwright's text, suggesting that it offers a critique of the British centralised state form and makes demands for the decentralisation of political power. Focussed on a small deindustrialised town, The Cut is an English regional polemic exploring how uneven development played a decisive role in the outcome of the European Union referendum. Building on Doreen Massey's insight that places are not simply physical locations but 'articulations of social relations' (Massey, 1994: 22 ), my discussion of Cartwright's novel is concerned with the way a discursive, cultural version of 'the North' was mobilised ideologically as a fulcrum of the Leave vote within Brexit media and political discourse. I trace the ways in which The Cut responds to this manoeuvre in an ambivalent deployment of nostalgia as both a vehicle for regional devolution and a literary mode associated with a parochial version of 'the North' that continues to exist in the national imagination. As this paper demonstrates, the text equivocates between a radical nostalgia that highlights the need for constitutional reform and a reactionary turn to the industrial past. Ultimately, I propose that The Cut forecloses its own devolutionary potential in an aesthetic and thematic reliance on cultural stereotypes of Northernness, suggesting the limitations of nostalgia as a resource for constructing alternatives to the present.